Simultaneous Determination of Iodide, Sulphate, Fluoride and Nitrite in Salt Samples by Ion Chromatography - Ning, Xia; Zhang, Ji-Hua (Asian Journal of Chemistry, 2014)
Simultaneous determination of iodide, sulphate, fluoride and nitrite in salt samples by ion chromatography was demonstrated in this paper. To avoid the interference of Cl–, solid Ag2O was used as a precipitator. After that, ascorbic acid was added to reduce the iodate to iodide ion. In the analysis process, IonPac·RAS19 4 × 250 mm was selected with IonPacAG19 4 × 50 mm as guard column. Leachate of potassium oxide solution was used with 1 mL/min flow velocity. Linearity ranges of iodide, sulphate, fluoride and nitrite were 0.1-10, 0.05-1, 0.01-0.80 and 0.01-0.80 μg/mL, respectively and high correlations (R2) were all above 0.999. Limits of detection (LOD) were 10 mg/kg (iodide ion), 5 mg/kg (sulphate), 1 mg/kg (fluoride) and 1 mg/kg (nitrite). This method is simple and convenient with rapid, accurate and high sensitivity which could be accepted in daily analysis.